Professional Ethics of Elementary School Teachers: Balancing Academic Demands and Students' Emotional Needs - Kurniawan, Machful Indra; Wulandari, Ria (Widyagogik, 2024)
Professional ethics play a vital role in creating a harmonious learning environment, especially at the primary school level. This study aims to explore how primary school teachers balance academic demands with students' emotional needs in their daily practices. The research employs a qualitative approach using a case study method in three different primary schools. The data were collected through in-depth interviews, classroom observations, and analysis of supporting documents, such as lesson plans and interview recording with parents. The data were analyzed using data reduction, data presentation, conclusion drawing and verification, thematic analysis, data triangulation, and narrative analysis to delve deeper into teachers' personal stories and experiences. The findings indicate that the teachers had moral dilemmas in meeting the curriculum targets or in addressing students' emotional needs. Some teachers successfully integrated both through the flexible approaches, such as project-based learning that emphasized the collaboration and empathy. However, some challenges emerged, such as having time constraints, dealing with administrative workloads, and the lack of specialized training in professional ethics were identified.